PILAR - PILAR DAKWAH PERSPEKTIF TAFSIR SURAT AL-FATIHAH - Sunardi Bashri Iman (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2023)
This research is intended to find out what da'wah contains in Surah Al-Fatihah implicitly. This qualitative research is in the nature of library research using the method of analyzing the da'wah values implied in Al-Fatihah with primary data sources of commentary books enriched with data insights originating from the da'wah discipline, then what becomes secondary data is a theme that is in line with the research This comes from scientific journals and trusted sites. As the findings of the author's analysis of Surah Al-Fatihah, seven cases were found which became elements of da'wah, first; Da'wah begins with and because of Allah SWT, secondly; Full of compassion in preaching, third; Hereafter oriented in preaching, fourth; Da'wah is worship, fifth; Da'wah is loaded with Divine help, sixth; Da'wah means commitment to the path of God Almighty and the seventh; Preaching should not be tempted by seduction from the right or the left.